Pernak-pernik Penelitian Etnoarkeologi di Papua 2005-2009 - Mahmud, M. Irfan (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
There are only few places in the world which still have the analogy materials that could connect two far different era, and one of them is Papua. From the linguistics aspect, Papua has approximately 300 tribes, such as Dani, Asmat, Marind-Anim, Hattam, Ekagi, and Sentani. From those hundreds tribes, the ethnoarchaeological researches in Papua have explored some aspects of analogy-archaeology materials, such as: religion, totem and symbol, habitation, governmental system, and ethnic-musicology. Based on the past 5 years (2005-2009) research, it is turned out that the research programs which have the tendency on ethnoarchaeology reached 75% or 18 from 24, though the effort on bringing the ’analogy’ materials to be analyzed deeply (thick description) is still facing several problems, particularly on human resources, methodology, and planning socialization aspects. Therefore, the RIPAN research format review surely needs to be done so that in the future it could be applied by the archaeologists.